ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PEMBENTUKAN HARGA BERAS DI INDONESIA - Desi Setiawati; Edmon Daris; Mudatsir Najamuddin (AGRIBUSINESS JOURNAL, 2018)
The test results obtained a value of adjusted Rsquare of 90.76%. These results indicate that the formation of rice prices in Indonesia can be explained by the independent variables used in the model is the production of rice, rice consumption, the price of imported rice, and the exchange rate of rupiah against the US dollar by 90.76%. While the remaining 9.24% is explained by other variables outside this research model. The joined test results indicate variables of domestic rice production, domestic rice consumption, the price of imported rice, and the exchange rate against the US dollar affect the formation of prices of rice in Indonesia with a value of F (42.77) is greater than F table (3.18 ) or probability value is 0.000000 <0.05. Partial test results found that the variable domestic rice production, domestic rice consumption, and the rupiah against the US dollar respectively significantly affect the domestic rice price variables at α = 0.05, whereas the variable import prices did not significantly affect variable domestic rice prices.